2016
DOI: 10.1371/journal.pone.0157483
|View full text |Cite
|
Sign up to set email alerts
|

Statins Inhibit Fibrillary β-Amyloid Induced Inflammation in a Model of the Human Blood Brain Barrier

Abstract: BackgroundAstrocytes and cerebral endothelial cells are important components of the blood-brain barrier (BBB). Disruption to this barrier through inflammation is a major contributor to Alzheimer’s disease (AD) pathology. The amyloid beta (Aβ) protein is known to exist in several forms and is a key modulator of AD that is known to cause inflammation and changes to BBB function. While one of these forms, fibrillary Aβ (fAβ), is known to cause endothelial cell death at the BBB, no studies have looked specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 70 publications
2
24
0
Order By: Relevance
“…Previous studies have shown that in the BBB, high concentrations of fAβ are toxic to microvascular endothelial cells and astrocytes [ 4 , 7 , 16 ]. In the present study, changes in cell viability of hBMECs and hAs were evaluated using a 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxy-phenyl)-2-(4-sulfophenyl)-2 H -tetrazolium (MTS) assay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that in the BBB, high concentrations of fAβ are toxic to microvascular endothelial cells and astrocytes [ 4 , 7 , 16 ]. In the present study, changes in cell viability of hBMECs and hAs were evaluated using a 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxy-phenyl)-2-(4-sulfophenyl)-2 H -tetrazolium (MTS) assay.…”
Section: Resultsmentioning
confidence: 99%
“…In AD, a number of different forms of Aβ peptides are present. Monomeric, oligomeric and fibrillary Aβ toxicity to endothelial cells of cerebrovascular origin has been claimed [ 13 , 15 , 16 ]. Previous reports have shown that, in both animal models and in cell culture models, fAβ caused cell death in BBB endothelial cells [ 4 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, GGPP has a beneficial role in amyloid processing by regulating the active γ‐secretase complex and membrane raft association . A reduction of GGPP results in neurite loss , and this could be one of the reasons for adverse effects of statins . Other, presumably isoprenoid‐unrelated mechanisms: protective role on BBB integrity in the presence of Aβ , stimulation of neurotrophins , and mitochondrial dysfunction .…”
Section: Medications With Potential Effects On the Brain Cholesterol mentioning
confidence: 99%
“…Similarly, simvastatin was shown to protect BBB integrity and attenuate neuropathophysiology and oxidative stress in APP transgenic AD mice [126]. In line with the latter, an in vitro study using human cerebral microvascular endothelial cells showed that simvastatin and lovastatin attenuated Aβ-induced BBB dysfunction [85]. Moreover, in a mouse model of dietary- induced BBB dysfunction, we demonstrated that atorvastatin and pravastatin reversed the disruption of BBB integrity [86].…”
Section: Antioxidants Cognitive Decline and Blood-brain Barriermentioning
confidence: 69%